(untitled) (DIGITAL TRANSFORMATION AND ARTIFICIAL INTELLIGENCE, 2025)
The article focuses on seismic excitation models and methods for generating and processing seismic records. Synthetic accelerograms were developed using probabilistic and stochastic methods following Eurocode 8 standards. The study addresses the correction of baseline errors in accelerograms to ensure accurate velocity and displacement values. Fourier Transform methods are applied to analyze temporal responses. A proposed model incorporates P and S waves with varying incidence angles and amplitudes to assess their effects on structures. The article also presents a method for calculating transfer functions and transitioning between time and frequency domains. The work enhances seismic analysis accuracy and contributes to safer structural design in earthquake-prone areas.